"DOES FEMINISM HAVE A GENERATION GAP?": blogging, millennials and the hip hop generation. Issue 1 (2nd January 2017) - Winch, Alison
Abstract: This article explores a number of instances when generation is invoked and discussed in three feminist blogs: the UK The Vagenda (2012–), the US-based Crunk Feminist Collective (2010), and the UK Feminist Times (2013–14). More specifically, it examines how generation is discussed in terms of a feminist identity, especially in relation to intergenerational conflict. I contextualize a textual analysis of these blogs within a conjunctural and intersectional understanding of generation. That is, I look at how these narratives of intergenerational feminism are produced or emerge from specific UK and US historical conditions, and the organization of social forces within them. I also look at how they map on to popular media discourses about generation. In addition, this article explores the ways in which generational identity intersects with categories of race, gender, class, sexuality and place.